Estimating mental health impacts of alcohol’s harms from other drinkers: Using propensity scoring methods with national cross-sectional data from the U.S - Karriker-Jaffe, Katherine J. (Addiction, 2018)
BACKGROUND & AIMS: Alcohol’s harms to others (AHTO) may cause substantial distress, particularly when harms are perpetrated by close others. One challenge to identifying causal impacts is that people harmed by drinkers differ in many ways from those not so harmed, so our aim was to assess mental health in relation to two serious types of AHTO, financial harm and assault by someone who had been drinking, using propensity score (PS) weighting to adjust for potentially confounding differences. DESIGN: Cross-sectional, nationally-representative, random sample of adults. SETTING: United States (U.S.). PARTICIPANTS: 76 respondents reporting financial harm compared to 4,625 with no past-year AHTO; 192 respondents reporting assault compared with 4,623 with no past-year AHTO. MEASUREMENTS: Predictors were reported exposure to financial problems due to someone’s drinking and assault by someone who had been drinking. Mental health outcomes were quality of life, distress and positive affect. Confounders included family history of alcohol problems, child physical/sexual abuse, substance use/dependence, impacts of recent economic recession, racial/ethnic discrimination, poverty, and other demographics. RESULTS: In double-robust PS weighted models, for financial harm, there were associations with reduced quality of life (B=−0.28, p=.02) and increased distress (aOR=4.69, p<.001), and for assault by a partner or family member, there were associations with increased distress (aOR=2.23, p=.09). For assault by a friend or stranger, none of the associations were statistically significant after PS weighting (all p>.10). CONCLUSIONS: Financial troubles due to someone else’s drinking and assaults perpetrated by drinking intimates (spouses, other partners or family members) were associated with poor mental health.